(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In this article, we problematize the theatrical fundamentals in site-specific theater to weave knowledge that helps in the practical and conceptual assimilation of this contemporary poetics. To this end, we start with theoretical approaches, creative distinctions, and historical examples of Brazilian theater.